The Lack of Gender Mainstreaming on the Presidential Regulation No. 86/2018 on Agrarian Reform - Nurdin, Iwan; Pasha, Julian Aldrin (Jurnal Perempuan, 2019)
The situation of agrarian injustice in the rural area carries multiple layers of burden on women. Such situation could be addressesd with the agrarian reform’s agenda. This is the reason why the society welcome the announcement of agrarian reform agenda as Joko Widodo administration’s priority program. After being in power for four years, finally the government had issued the Presidential Regulation No. 86 year of 2018 on Agrarian Reform. The enactment of this Agrarian Reform’s policy cannot be separated from the role of social movement organizations in urging for agrarian reform agenda, including in urging for an agrarian reform policy with gender justice perspective. This paper seeks to see how women’s movement and the agrarian reform movement have been trying to advocate gender perspective in the formulation and the implementation of the Presidential Regulation (Perpres).